THE PORTRAYAL OF JAVANESE WOMEN FORTITUDE IN ENTROK BY OKKY MADASARI : (A MORAL MESSAGES ANALYSIS) - Nabila, Yugistia Azma; Thamrin, Husni; Supian, Supian (IPI Garut Press, 2022)
This study aims to show how the Javanese women's characteristics depict moral messages in a literary work. The research is entitled